(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current state of public knowledge, attitudes, and practices regarding the use of antibiotics among the Vietnamese population. Methods: A search strategy for full-text publications on Google Scholar and PubMed was employed. The full-text articles identified were screened according to the PRISMA flow diagram, with 15 articles published from January 2019 to February 2025 selected for inclusion in the review report. Results: Self-medication with antibiotics without a prescription is very common in Vietnam, and the public receives very limited counseling on proper antibiotic use. The levels of knowledge, attitudes, and practices concerning the use of antibiotics and antimicrobial resistance among the public are inconsistent and suboptimal; there is an association between perceptions of antibiotic use and antimicrobial resistance with demographic factors, educational level, economic conditions, and family size. The studies only described the current situation. Conclusion: Educational campaigns are needed to enhance community knowledge about the use of antibiotics and antimicrobial resistance; future research should focus on measures to raise public awareness regarding antibiotic use and antimicrobial resistance, thereby contributing to the control of antimicrobial resistance in Vietnam.